MicroRNA‐130a inhibits proliferation of vascular smooth muscle cells by suppressing autophagy via ATG2B. Issue 8 (21st February 2021) - Zheng, Liang; Wang, Zhecun; Li, Zilun; Wang, Mian; Wang, Wenjian; Chang, Guangqi
Abstract: Numerous microRNAs participate in regulating the pathological process of atherosclerosis. We have found miR‐130a is one of the most significantly down‐regulated microRNAs in arteriosclerosis obliterans. Our research explored the function of miR‐130a in regulating proliferation by controlling autophagy in arteriosclerosis obliterans development. A Gene Ontology (GO) enrichment analysis of miR‐130a target genes indicated a correlation between miR‐130a and cell proliferation. Thus, cell cycle, CCK‐8 assays and Western blot analysis were performed, and the results indicated that miR‐130a overexpression in vascular smooth muscle cells (VSMCs) significantly attenuated cell proliferation, which was validated by an in vivo assay in a rat model. Moreover, autophagy is thought to be involved in the regulation of proliferation. As our results indicated, miR‐130a could inhibit autophagy, and ATG2B was predicted to be a target of miR‐130a. The autophagy inhibition effect of miR‐130a overexpression was consistent with the effect of ATG2B knockdown. The results that ATG2B plasmids and miR‐130a mimics were cotransfected in VSMCs further confirmed our conclusion. In addition, by using immunohistochemistry, the positive results of LC3 II/I and ATG2B in the rat model and artery vascular tissues from the patient were in accordance with in vitro data. In conclusion, our data demonstrate that miR‐130a inhibits VSMCs proliferation via ATG2B, which indicates that miR‐130a could be a potential therapeutic target that regulates autophagy in atherosclerosis obliterans.